The World Conference on Indigenous Peoples 2014 - Whare, Tracey (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The UN Special Procedures and Indigenous Peoples' Rights - Te Aho, Fleur (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Blunting the System: The Personal is Political - Sykes, Annette (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: activism; law; neoliberalism; waitangi tribunal

Indigenous Rights - Kingi, Pauline (The Treaty is always speaking: Te reo o te tiriti mai rano, 1989)
Keywords: civil Rights; history; human rights; indigenous rights; social life and customs; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Chapter 5: Political and Constitutional Implications of the Treaty - Rata, Matiu (The Treaty is always speaking: Te reo o te tiriti mai rano, 1989)
Keywords: civil Rights; history; social life and customs; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Race Relations and the Treaty: A Framework for Resolution - Gardiner, Wira (Partnership and peace: essays on biculturalism in Aotearoa - New Zealand, 1990)
Keywords: government; race relations; tiriti o waitangi/treaty of waitangi; waitangi tribunal

Te Tiriti me Ōna Whakatau: The Waitangi Tribunal and Treaty Settlements - Ruru, Jacinta (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: history; social conditions; social life and customs; tiriti o waitangi/treaty of waitangi; treaty settlements; tribunal reports; waitangi tribunal

The Wai 262 Claim: A Claim by Māori to Indigenous Flora and Fauna - Solomon, Maui (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty claims; treaty settlements; waitangi tribunal

Chapter 11: Recovering Fagin's Ill-Gotten Gains: Settling Ngāti Kahu's Treaty of Waitangi Claims Against the Crown - Mutu, Margaret (Waitangi Revisited, 2005)
Keywords: government relations; history; land tenure; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

Orakei - Kāwharu, Hugh (Waitangi Revisited, 2005)
Keywords: government relations; hapū; history; land tenure; ngāti whatua; political action; race relations; rangatiratanga; tiriti o waitangi/treaty of waitangi; tāngata whenua; waitangi tribunal

Chapter Four: The Treaty of Waitangi in the Postcolonial Era - Walker, Ranginui (Waitangi Revisited, 2005)
Keywords: colonisation; government relations; history; land march; land tenure; post-colonialism; race relations; tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

The "false generosity" of treaty settlements: innovation and contortion - Te Aho, Linda (International Indigenous Rights in Aotearoa New Zealand, 2017)
In Aotearoa New Zealand the ways in which indigenous claims to lands and waters are addressed are often looked to as good, or even best, practice by indigenous peoples around the world. While things are far from perfect, in recent decades Maori have succeeded in changing perceptions about the Treaty of Waitangi as the foundation of the nation, and work steadily continues on settling outstanding Treaty claims. The resulting Treaty of Waitangi settlements are negotiated arrangements which aim to remove a sense of historical grievance and achieve significant rebuilding of the Maori economy. They are seen by some as dynamic and powerful steps towards economic independence, as a means of recognising special relationships to lands and waters, and a necessary prerequisite to improved relationships between the state and the indigenous Maori in the future. ¹ Critics see the settlements and the processes followed to reach them as too heavily weighted in the government's favour. ² They argue that the settlements do not sufficiently compensate for actual losses. They are said to pit Maori against Maori. Diverse claimant groups are effectively forced to negotiate within standardised and fixed parameters. For these and other reasons, the settlement agreements, policies and processes have been labelled as divisive and compromising self-determination. ³
Keywords: tiriti o waitangi/treaty of waitangi; treaty settlements; waitangi tribunal

From new paternalism to new imaginings of possibilities in Australia, Canada and Aotearoa/New Zealand: Indigenous rights and recognition and the state in the neoliberal age - Bargh, Maria; Howard-Wagner, Deirdre; Altamirano-Jimenez, Isabel (The Neoliberal State, Recognition and Indigenous Rights, 2018)
The election of Evo Morales as the first indigenous President of Bolivia in 2005 is widely credited to the Cochamba Water War (Spronk 2007: 8). The Cochamba Water War progressed from an indigenous movement and a specific issue to the creation of an indigenous political party and election of the first indigenous President. The Bolivian water war, the Puebla Panama Plan in Mexico, the Mackenzie Valley pipeline in Canada (Altamirano‐Jiménez 2004) and Māori resistance to the neoliberal agenda from 1984 onwards (Bargh 2007: 26) inspired much theorising about indigenous people successfully contesting neoliberalism (AltamiranoJiménez 2004, Bargh 2007, Spronk 2007: 8, Postero 2007). Bargh and others, for example, documented not only ‘overt Māori resistance to neoliberal policies, but also more subtle stories of activities, which The neoliberal state, recognition and indigenous rights implicitly challenge neoliberal practices and assumptions by their support for other ways of living’ (Bargh 2007: 1). Scholars make visible the persistence of the colonial in the concrete and material conditions of everyday neoliberal governance and life (Howard-Wagner & Kelly 2011: 103). As Bargh (2007), Altamirano-Jiménez (2013), Howard-Wagner (2010b, 2015) and others note, indigenous categorisations of neoliberal practices as a form of colonisation relate to a concern that neoliberalism in its multiple forms poses a threat to indigenous ways of life. This scholarship also critically reflects on the reshaping of the relationship between the state and indigenous peoples under neoliberalism (Altamirano-Jiménez 2004, Bargh 2007, Howard-Wagner 2009). For example, it draws attention to the increasing intervention in the lives of indigenous peoples (Howard-Wagner 2007, 2009, 2010a, 2010b) and the dispossession of indigenous people through privatisation (Wolfe 2006, Howard-Wagner 2012, Altamirano-Jiménez 2013, Coulthard 2014). It does not, however, preclude agency, resistance and decolonisation. Interpretive micro-studies about indigenous peoples’ engagement with neoliberalism provide particular value. They tell us about actually existing neoliberalism in the context of intervention in the everyday lives of indigenous peoples, contests over rights, contests over policy and the complex decisions indigenous people are making about how to protect their rights and navigate diverse economies involving neoliberal policies and practices.
Keywords: crown policy; neoliberalism; treaty obligations; waitangi tribunal; water management; water rights